Interferon‐γ‐induced HLA Class II expression on endothelial cells is decreased by inhibition of mTOR and HMG‐CoA reductase. Issue 5 (15th April 2020) - Maenaka, Akihiro; Kenta, Iwasaki; Ota, Akinobu; Miwa, Yuko; Ohashi, Wataru; Horimi, Kosei; Matsuoka, Yutaka; Ohnishi, Masafumi; Uchida, Kazuharu; Kobayashi, Takaaki
Abstract : In organ transplantation, donor‐specific HLA antibody (DSA) is considered a major cause of graft rejection. Because DSA targets primarily donor‐specific human leukocyte antigen (HLA) expressed on graft endothelial cells, the prevention of its expression is a possible strategy for avoiding or salvaging DSA‐mediated graft rejection. We examined the effect of various clinically used drugs on HLA class II expression on endothelial cells. Interferon‐γ (IFN‐γ)‐induced HLA class II DR (HLA‐DR) was downregulated by everolimus (EVR, 49.1% ± 0.8%; P  < 0.01) and fluvastatin (FLU, 33.8% ± 0.6%; P  < 0.01). Moreover, the combination of EVR and FLU showed a greater suppressive effect on HLA‐DR expression. In contrast, cyclosporine, tacrolimus, mycophenolic acid, and prednisolone did not exhibit any significant suppressive effect. FLU, but not EVR, suppressed mRNA of HLA‐DR. Imaging analysis revealed that HLA‐DR expressed in cytosol or on the cell surface was repressed by EVR (cytosol: 58.6% ± 4.9%, P  < 0.01; cell surface: 80.9% ± 4.0%, P  < 0.01) and FLU (cytosol: 19.0% ± 3.4%, P  < 0.01; cell surface: 48.3% ± 4.8%, P  < 0.01). These data indicated that FLU and EVR suppressed IFN‐γ‐induced HLA‐DR expression at the transcriptional and post‐translational level, respectively, suggesting a potential approach for alleviating DSA‐related issues in organ transplantation. Abstract : Donor human leukocyte antigen (HLA)s on graft endothelial cells are targeted by donor‐specific HLA antibody (DSA), which is considered to be a major cause of antibody‐mediated rejection in organ transplantation. In this manuscript, it is suggested that the mTOR and HMG‐CoA reductase inhibitors suppress IFN‐γ‐induced HLA‐DR in endothelial cells. This finding may become the basis of a new approach for alleviating DSA‐related problems in organ transplantation.